Addressing the Demand for Cultural Relevance in Intervention Design. Issue 5 (September 2014) - Keller, Colleen S.; Coe, Kathryn; Moore, Nancy
This article describes the development of a model to promote physical activity in Hispanic women that embeds a life course perspective and culture to enhance comparative effectiveness in intervention design. When working with diverse cultural groups, researchers often struggle with intervention designs and strategies to enhance cultural relevance; they do so based on the assumption that this will enhance efficacy and make interventions more sustainable. In this article, the authors discuss how the model was used in two interventions designed for younger and older Hispanic women. These interventions were guided by a life course perspective, incorporated social support, and included salient elements from the women's culture. Three considerations underpinned the development of the model: (a) infusing concepts and values of a culture and tradition into the interventions, (b) viewing participants through a life course perspective to assess how an intervention can build on developmental transitions, and (c) determining how social support operates within two groups that, although sharing history and thus some cultural practices, diverge widely in those practices. The authors propose that by incorporating elements of this model into their interventions, researchers can increase program efficacy and effectiveness.